2021
DOI: 10.1155/2021/4736670
|View full text |Cite
|
Sign up to set email alerts
|

Sanse Powder Essential Oil Nanoemulsion Negatively Regulates TRPA1 by AMPK/mTOR Signaling in Synovitis: Knee Osteoarthritis Rat Model and Fibroblast-Like Synoviocyte Isolates

Abstract: Synovitis is the primary driving factor for the occurrence and development of knee osteoarthritis (KOA) and fibroblast-like synoviocytes (FLSs) and plays a crucial role during this process. Our previous works revealed that transient receptor potential ankyrin 1 (TRPA1) ion channels mediate the amplification of KOA synovitis. In recent years, essential oils have been proved to have blocking effect on transient receptor potential channels. Meanwhile, the therapeutic effect of Sanse Powder on KOA synovitis has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Some investigators have also demonstrated the anti-inflammatory activity of EO NE using models of arthritis. Li et al [63] prepared a sanse powder EO NE (SP-NE) and also found less inflammatory cell infiltration in the synovial tissue of osteoarthritis rats treated with SP-NEs. Similar results were reported by Mohammadifar et al [64].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Some investigators have also demonstrated the anti-inflammatory activity of EO NE using models of arthritis. Li et al [63] prepared a sanse powder EO NE (SP-NE) and also found less inflammatory cell infiltration in the synovial tissue of osteoarthritis rats treated with SP-NEs. Similar results were reported by Mohammadifar et al [64].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…These ndings suggest that deferoxamine can mitigate osteoarthritis caused by iron overload, yet its impact on the M1 polarization of synovial macrophages due to iron overload remains unexplored. Given the crucial role of the mTORC1-p70S6K/4E-BP1 pathway in M1 macrophage polarization and synovitis promotion [25,26], and the potential for intracellular iron to activate this pathway [27], this study aims to demonstrate that deferoxamine can reduce synovial iron overload by inhibiting the mTORC1-p70S6K/4E-BP1 pathway, thereby suppressing M1 macrophage polarization, decreasing pro-in ammatory cytokine secretion, and alleviating hemophilic synovitis.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that l -carnitine supplementation can reduce synovial inflammation and cartilage destruction and alleviate pain at the central and peripheral levels [ 22 ]. Our previous work also addressed the role of fibroblast-like synoviocytes (FLS) in AMPK signaling during KOA, accordingly suggesting that these cells promote both the onset and the progression of synovitis by regulating AMPK Signaling [ 23 ]. When LPS-induced inflammatory responses in FLS occur, TRPA1-mediated Ca 2+ influx is enhanced and IL-1β, TNF-α expression is increased [ 24 ].…”
Section: Introductionmentioning
confidence: 99%